POST-GADDAFI REPERCUSSIONS IN NORTHERN MALI (The Strategic Review for Southern Africa, 2020)
While utopias of (political) autonomy or an independent (Tuareg) state have for long been part and parcel of internal debates among Tuareg, it was only recently that the claim for independence was formulated to the outside world. A Tuareg state, Azawad, was even put into practice, albeit for some months only. A second characteristic is that there has never been a serious attempt at integrating all Tuareg, regardless of the country they are living in, into a unique nation-state. Is the 'national identity' of the respective post-colonial states so strong that it supplants the 'claim for independence'? Or is the pre-colonial form of political organisation among Tuareg, the regional drum-group (ettebel), still so vivid that it impedes the establishment of a state that would encompass all Tuareg? Apart from the independence movement MNLA (Mouvement National pour la Libération de l'Azawad) operating in Northern Mali, there are Islamist groups which fight for the spread of an Islamic mode of life. Some of these succeeded in recruiting Tuareg, particularly among the Tuareg of the Kidal region. The appeal of the 'Islamic claim' to the Kidal Tuareg goes back to their genesis as a political entity during the period of colonial conquest when the French installed a regional 'drum-group' within the framework of administrative chieftainship. As nearly all regional Tuareg claim descent from members of the Islamic army that conquered North Africa in the 7th century, regional power differs from power structures in all other regions inhabited by Tuareg. It is based on a double legitimacy: that of Islamic nobility, and that of the Tuareg warrior class. For several months, however, there has been ideological dissent among the Tuareg followers of the Islamic movements. This debate revolves around several issues, particularly the question as to whether or not the Islamic mode of life is to be limited to the sole region of Kidal.